Knowledge of God and the development of early Kabbalah - Dauber, Jonathan. (Supplements to The Journal of Jewish Thought and Philosophy, 2012)
In Knowledge of God and the Development of Early Kabbalah , Jonathan Dauber offers a fresh consideration of the emergence and early development of Kabbalah against the backdrop of a re-evaluation of the relationship between early Kabbalistic and philosophic discourse. He argues that the first Kabbalists adopted a philosophic ethos that was foreign to traditional Rabbinic Judaism but had taken root in Languedoc and Catalonia under the influence of newly available philosophical materials. In this ethos, the act of investigating God was accorded great religious significance, and it was its adoption by the first Kabbalists that helped spur them to engage in their investigations of God and, in so doing, develop Kabbalah.